Model Decision Tree Analysis dalam Penerapan Manajemen Risiko Studi Kasus: Webinar Kerja, Kerja, Tipes! pada Tahun 2021 oleh Seemore Event Organizer - Nadya Dwi Yanti (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2023)
During the COVID-19 pandemic, event organizing activities in Indonesia switched from the concept of being online (virtual). The virtual event activities that were rife at that time were online seminars or webinars with different themes and speakers. In December 2021, Seemore Event Organizer in collaboration with a psychology consulting company called Arsanara has also successfully held a webinar event with the theme of toxic productivity in the world of work entitled